Application of a nurse‐led transitional care programme for patients discharged with T‐tubes after biliary surgery - Meng Wang; Jieyu Hua; Yanli Liu; Tao Liu; Hongyin Liang (Wiley, 2023)
Abstract Aim Nurse‐led transitional care programmes (TCPs) have been shown to facilitate patient recovery in several illness settings, but its role among patients discharged with T‐tubes remains uncertain. The aim of the study was to investigate the effects of a nurse‐led TCP among patients discharged with T‐tubes. Design This retrospective cohort study was conducted at a tertiary medical centre. Methods From January 2018 to December 2020, a total of 706 patients discharged with T‐tubes after biliary surgery were included in the study. Patients were divided into a TCP group (n = 255) and a control group (n = 451) based on whether they participated in a TCP. The baseline characteristics, discharge readiness, self‐care ability, transitional care quality and quality of life (QoL) were compared between the groups. Results Self‐care ability and transitional care quality were significantly higher in the TCP group. Patients in the TCP group also exhibited improved QoL and satisfaction. The results suggest that the incorporation of a nurse‐led TCP among patients discharged with T‐tubes after biliary surgery is feasible and effective. No Patient or Public Contribution.